2006
DOI: 10.1111/j.1600-0420.2006.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability (test‐retest variability) of refractive error measurement in clinical settings

Abstract: ABSTRACT.Purpose: To estimate the repeatability of refractive error measurement (REM) in a clinical environment in cataractous, pseudophakic and healthy eyes. Methods: The refractive error of patients referred for cataract surgery or consultation measured by ophthalmic professionals was re-examined and the measurement results were compared. A total of 99 eyes from 99 persons (41 cataractous, 36 pseudophakic and 22 healthy eyes) with visual acuity (VA) of 0.3-1.3 (logMAR 0.52 to ) 0.11) were included. The diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 23 publications
2
40
1
1
Order By: Relevance
“…Only patients with high best-corrected visual acuity were enrolled, which makes refraction assessment repeatable. 19 To evaluate the outcome in astigmatism, we developed a number of optical equations based on the Naeser polar value concept.…”
Section: Discussionmentioning
confidence: 99%
“…Only patients with high best-corrected visual acuity were enrolled, which makes refraction assessment repeatable. 19 To evaluate the outcome in astigmatism, we developed a number of optical equations based on the Naeser polar value concept.…”
Section: Discussionmentioning
confidence: 99%
“…These may include differences in capsulorhexis configuration, the actual postoperative ACD (positioning of the IOL) of individual eyes, differences in wound healing processes, variability of the time interval required to reach refractive stability, and errors related to the measurement of postoperative refraction. However, it seems that some of these factors are not measurable and thus are not controllable; it has also been suggested that some are inevitable 31,36. Despite these limitations, we hope that our study will provide valuable guidance in the interpretation and application of biometric data obtained by the IOL Master® in current clinical settings.…”
Section: Discussionmentioning
confidence: 91%
“…The SD of manual refraction was estimated to be one quarter of the 95% limits of agreement, or 0.39 D, as determined by Bullimore et al 15 This is of the same order of magnitude as in a recent study by Leinonen et al, 26 who found 0.37 D, again estimated as one quarter of the 95% limits in a mixed group (n Z 99) of healthy, pseudophakic, and cataractous patients. In patients with a visual acuity of 0.7 or better (z20/30) they found 0.25 D, but the difference was not statistically significant.…”
Section: Postoperative Refractionmentioning
confidence: 99%